Histopathologic and clinicopathologic classifications of antineutrophil cytoplasmic antibody-associated glomerulonephritis: a validation study in a Korean cohort - Lim, Jeong-Hoon (Kidney Res Clin Pract, 2021)
BACKGROUND: Antineutrophil cytoplasmic antibodies (ANCA)-associated glomerulonephritis (AAGN) is a common cause of rapidly progressive glomerulonephritis and requires prompt and proper immunosuppressive therapy to improve renal prognosis. This study aimed to evaluate the predictive value of two different classifications for renal outcomes in Korean AAGN patients. METHODS: Ninety-two patients who were diagnosed with AAGN at two tertiary hospitals between 2004 and 2018 were retrospectively analyzed retrospectively. The histopathologic classification according to glomerular pathology and the clinicopathologic classification according to normal glomeruli ratio, degree of interstitial fibrosis/tubular atrophy, and baseline renal function were evaluated using the Cox proportional hazards model. RESULTS: Forty-five patients (48.9%) progressed to end-stage kidney disease (ESKD) during the observation period. The mean age was 61.0 ± 15.3 years, and most patients had myeloperoxidase-ANCA (93.5%). In the histopathologic classification, the best renal survival occurred in the focal class, whereas the sclerotic class had the worst renal survival (sclerotic class vs. focal class; adjusted hazard ratio [aHR], 5.05; 95% confidence interval [CI], 1.32–19.31; p = 0.018). The mixed class had intermediate renal outcomes (mixed class vs. focal class; aHR, 4.23; 95% CI, 1.23–14.58; p = 0.022). In the clinicopathologic classification, the high-risk group had poor renal outcomes compared with the low-risk group (aHR, 6.56; 95% CI, 1.25–34.26; p = 0.026), but renal outcomes did not differ between the low- and medium-risk groups. CONCLUSION: In Korean AAGN patients, histopathologic and clinicopathologic classifications had predictive value for renal outcomes, especially in the sclerotic class or the high-risk group with higher risk of progression to ESKD despite treatment.